Critical factors affecting student satisfaction in distance learning environment: a review of the literature - Amoozegar, Azadeh; Mohd Daud, Shaffe; Mahmud, Rosnaini; Ab. Jalil, Habibah (Universiti Putra Malaysia Press, 2018)
Distance education is usually applied in several parts of the world to provide study opportunities for those who cannot or do not attempt to be involved in classroom instruction. According to some educators, distance education is considered as one of the most important and significant new instructional approaches available for improving teaching and learning in universities nowadays. This has raised important questions about the determining factors which influence learning, satisfaction, and retention of the learners of this academic program because a key concern for most institutions and teachers is whether learners are satisfied with their learning experience or not. Hence, there is a need to study more and in depth on distance education to overcome the types challenges, issues, and identifying factors that influence student satisfaction with online courses. In this paper, the authors review the current literature and discuss possible factors in order to provide appropriate support for suitable distance learning environment to positively affect student satisfaction with online courses.